A framework for conceptualizing and modeling social-ecological systems for conservation research. (November 2022) - Anderies, John M.; Cumming, Graeme S.; Clements, Hayley S.; Lade, Steven J.; Seppelt, Ralf; Chawla, Sivee; Müller, Birgit
Abstract: As conservation biology has matured, its scope has expanded from a primarily ecological focus to recognition that nearly all conservation problems involve people. At the same time, conservation actions have been increasingly informed by ever more sophisticated quantitative models. These models have focused primarily on ecological and geographic elements of conservation problems, such as mark-recapture methods, predicting species occurrences, and optimizing the placement of protected areas. There are many off-the-shelf ecological models for conservation managers to draw upon, but very few that describe human-nature interactions in a generalizable manner. We address this gap by proposing a minimalistic modeling framework for human-nature interactions, combining well-established ideas in economics and social sciences (grounded in Ostrom's social-ecological systems framework) and accepted ecological models. Our approach begins with a systems breakdown consisting of an ecosystem, resource users, public infrastructure, and infrastructure providers; and interactions between these system elements, which bring together the biophysical context, the relevant attributes of the human society, and the rules (institutions, such as protected areas) currently in use. We briefly review the different disciplinary building blocks that the framework could incorporate and then illustrate our approach with two examples: a detailed analysis of the social-ecological dynamics involved in managing South African protected areas and a more theoretical analysis of a general system. We conclude with further discussion of the urgent need in conservation biology for models that are genuinely designed to capture the complexities of human socioeconomic behavior, rather than the more typical approach of trying to adapt an ecological model or a stochastic process to simulate human agency and decision-making. Our framework offers a relatively simple but highly versatile way of specifying social-ecological models that will help conservation biologists better represent critical linkages between social and ecological processes when modeling social-ecological dynamics. Highlights: A framework for conceptualizing and modeling social-ecological systems is presented. Supporting modeling 'building blocks' are presented for conservation problems. Application of the framework is illustrated for two conservation problems. Utility of the framework for improving conservation outcomes is discussed.